Biobutanol Production by Clostridium acetobutylicum ATCC 824 Using Oil Palm Frond (OPF) Juice - Nur Syazana, Muhd Nasrah; Mior Ahmad Khushairi, Mohd Zahari; N., Masngut (2016)
The aim of the present paper is to study the production of biobutanol from oil palm frond (OPF) juice by Clostridium acetobutylicum ATCC 824. The fermentation was carried out anaerobically in batch mode. The effect of total sugars concentration in OPF juice (10 – 60 g/L), temperature (32 – 42 oC), and initial pH (5 – 7) were investigated. The highest biobutanol yield (0.24 g/g) was obtained at 50 g/L of total sugars concentration, 37oC, and pH 6 with a biobutanol production value as high as 9.24 g/L. However, the production decreased to 3.09 g/L with a yield of 0.13 g/g when a higher value of initial total sugars concentration (60 g/L) was used. On the other hand, the production yield also low when the fermentation conditions were set at 42oC (0.04 g/g) and pH 5 (0.13 g/g). The results presented herewith showed that OPF juice is promising as a renewable carbon source for biobutanol production. The suitable fermentation environment can enhance the yield of biobutanol production.